PHOTOCATALYTIC DEGRADATION OF RHODAMINE B USING Ag NANO DOPED TiO2 PREPARED BY -IRRADIATION METHOD - Nhu, Vo Thi Thu; Duy, Nguyen Ngoc; Tuan, Huynh Nguyen Anh; Ngan, Nguyen Pham Tu; Minh, Do Quang; Hien, Nguyen Quoc (Vietnam Journal of Science and Technology, 2016)
Ag nano deposited on TiO2 (Degussa P25) (Ag nano/TiO2) photo-catalyst has been synthesized by g-irradiation method. The  characteristics  of  Ag nano/TiO2 material  has  been  investigated  by BET surface area, X-ray diffraction (XRD), transmission electron microscopy (TEM) and the diffuse reflectance spectra (DRS). The photo-catalytic properties of Ag nano/TiO2 for degradation of Rhodamine B in aqueous solution under visible light have been studied. Results indicated that Ag nano/TiO2 photo-catalyst exhibited better photo-catalytic activity compared to that of TiO2 under the same reaction condition. The higher activity of Ag nano/TiO2 is due the enhancement of electron–hole separation effect on the surface of the catalyst. At 1.5% Ag doping content, the Ag nano/ TiO2 photo-catalyst exhibited the highest photo-catalytic activity under visible light.